Pectinase Production by Bacillus and Paenibacillus sp. Isolated from Decomposing Wood Residues in the Lagos Lagoon - Busayo Tosin Akinyemi; Olanike Maria Buraimoh; Olayemi Omowunmi Ogunrinde; Olukayode Oladipo Amund (Journal of Tropical Life Science, 2017)
Three wood decomposing bacteria isolated from the Lagos lagoon, Bacillus megaterium, Bacillus bataviensis and Paenibacillus sp. were screened for their pectinase producing abilities using pectin as substrate under submerged fermentation (SMF) conditions. The results showed that all three isolates produced appreciable pectinolytic activities. Paenibacillus sp. showed the highest pectinase activity when compared with the other two isolates. The optimum pH for pectinase activity for both B. megaterium and B. bataviensis was 8.0 while it was 6.5 for Paenibacillus sp., B. bataviensis, and B. megaterium showed optimum pectinase activity at 60Â°C and Paenibacillus sp. at 40Â°C. Metal ions such as Na+ and K+ improved the activity of pectinase produced by the three isolates when compared to the effect of Zn2+ and Mn2+. The molecular weights of the enzymes were also estimated by gel filtration as 29,512 da, 32,359 da, and 25,119 da for Paenibacillus sp., B. megaterium and B. bataviensis respectively. The study has provided a platform for further investigation into the biochemical characterization of the enzyme, and optimization of culture conditions to scale up pectinase production for commercial exploitation.